To expand \( \frac{7}{4} ( 8h + 3 ) \), you distribute \( \frac{7}{4} \) to both terms inside the parentheses:
\[ \frac{7}{4} \times 8h + \frac{7}{4} \times 3 \]
Now, calculate each term:
-
For the first term: \[ \frac{7}{4} \times 8h = \frac{7 \times 8h}{4} = \frac{56h}{4} = 14h \]
-
For the second term: \[ \frac{7}{4} \times 3 = \frac{7 \times 3}{4} = \frac{21}{4} \]
Now, combine both results:
\[ 14h + \frac{21}{4} \]
So, the expanded form of \( \frac{7}{4} ( 8h + 3 ) \) is:
\[ 14h + \frac{21}{4} \]